CLINICAL FEATURES IN MATERNAL FETAL PREMATURITY AND GROWTH RETARDATION - Pacheco Romero, José (2015)
Between July and December 1981 they were treated 202 preterm infants (P) and 105 newborns with intrauterine growth retardation (IUGR), with incidences 2 0.7 and 1.4 per 1000 live births, respectively. The baby's mother with primigravida RCJU and tended to be slightly younger, had better pre-natal period shorter internatal control. They were important precedents in both groups, abortion, cesarean section (15%) and urinary tract infection. They noted as complications of pregnancy hypertension, anemia and urinary tract infection. In prematurity, they were also determining twinning and rupture of membranes. There was high incidence of dystocia in both groups, mainly cesarean: 29% P and 44% in IUGR. The Apgar was lower in P, where perinatal mortality 178 per thousand in P and 85 per thousand in IUGR. 7 .6 percent of babies with IUGR had congenital malformations. The findings are discussed and the literature is reviewed, becoming a reflection on the diagnosis and appropriate management of these cases and the possible consequences of caesarean section over prematurity and IUGR in subsequent pregnancies, especially if the period is short internatal a malnourished women.